Liposomes Under Shear: Structure, Dynamics, and Drug Delivery Applications. Issue 4 (5th February 2023) - Karaz, Selcan; Senses, Erkan
Abstract : The targeted delivery to specific locations while not causing damage to healthy tissues efficiently remains a challenge in drug delivery systems. Through addressing this issue, stimuli‐responsive materials have been under investigation. As one of the fundamental forces associated with blood flow, shear stress is taken as an advantage to design shear‐sensitive drug carriers. Although blood flow is modeled as laminar flow under normal conditions, in case of constrictions caused by endothelial shear stress, cardiovascular diseases, or angiogenesis due to tumor formation, local shear stress can dramatically increase. To date, shear‐sensitive materials have been investigated under two main categories: shear‐disaggregated and shear‐deformed nanoparticles based on their structural mechanism after exposure to high‐shear stress. Among them, liposomes are promising materials with their soft and deformable structure, high biocompatibility, controlled‐release properties, and sensitivity to shear stress. Herein, in this review, the effects of shear stress on liposomes in terms of their structural changes, flow regimes, rheological properties, and drug delivery applications are discussed. It is believed that this work provides a basis for designing more effective drug delivery systems considering the complexity of the human body. Abstract : Herein, the effects of shear stress on liposomes in terms of structure, flow regimes, rheological properties, and drug delivery applications are summarized. This review is expected to provide a basis for designing new shear‐triggered liposomal drug release systems and complement the current research on smart delivery systems responsive to physiological and external stimuli, including temperature, electromagnetic field, ultrasound, etc.